2013
DOI: 10.5513/jcea01/14.1.1163
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the semi-leafless field pea on dry matter yield

Abstract: The field pea breeding at the Agricultural Institute Osijek has primarily been aimed at continued development of new cultivar types with high yield, potential early group maturity and resistance to lodging. Letin is a new semi-leafless -winter field pea (Pisum sativum) with purple flowers and a mottled light brown seed coat. Semileafless and leafed genotypes were evaluated for plant height, lodging, maturity, forage yield and quality in two locations. The forage yield of pea genotypes has an average of 32.21 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The results are contradictory: when studying six field pea genotypes (two semi-leafless and four normal-leafed) in eight environments for dry matter and seed yield, Acikgoz et al (2009) concluded that the semi-leafless cultivars newly registered at that time in Turkey had a significant 6% seed yield advantage over the normal-leafed genotypes. Studies by Cupic et al (2013) illustrated that normal-leafed pea cultivars had a lower forage and dry matter yield but higher protein content, though these results were not consistent over different seasons. Narits (2008) reported that semi-leafless cultivars had a higher seed yield (cited in Olle, 2017a), but this was not evident in the investigation of Olle (2017b).…”
Section: Core Ideasmentioning
confidence: 93%
See 1 more Smart Citation
“…The results are contradictory: when studying six field pea genotypes (two semi-leafless and four normal-leafed) in eight environments for dry matter and seed yield, Acikgoz et al (2009) concluded that the semi-leafless cultivars newly registered at that time in Turkey had a significant 6% seed yield advantage over the normal-leafed genotypes. Studies by Cupic et al (2013) illustrated that normal-leafed pea cultivars had a lower forage and dry matter yield but higher protein content, though these results were not consistent over different seasons. Narits (2008) reported that semi-leafless cultivars had a higher seed yield (cited in Olle, 2017a), but this was not evident in the investigation of Olle (2017b).…”
Section: Core Ideasmentioning
confidence: 93%
“…Studies by Cupic et al. (2013) illustrated that normal‐leafed pea cultivars had a lower forage and dry matter yield but higher protein content, though these results were not consistent over different seasons. Narits (2008) reported that semi‐leafless cultivars had a higher seed yield (cited in Olle, 2017a), but this was not evident in the investigation of Olle (2017b).…”
Section: Introductionmentioning
confidence: 94%
“…The results are contradictory: When studying six field pea genotypes (two semi-leafless and four normal-leafed) in eight environments for dry matter and seed yield, concluded that the semi-leafless cultivars newly registered at that time in Turkey had a significant 6% seed yield advantage over the normal-leafed genotypes. Studies by Cupic et al (2013) illustrated that normal-leafed pea cultivars had a lower forage and dry matter yield but higher protein content, though these results were not consistent over different seasons. reported that semi-leafless cultivars had a higher seed yield (cited in Olle, 2017a), but this was not evident in the investigation of Olle (2017b).…”
Section: Introductionmentioning
confidence: 93%